2004
DOI: 10.1080/15476910490438351
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Effector Mechanisms in Animal Models of Occupational Asthma

Abstract: Occupational asthma is a form of immunotoxicity resulting from an exaggerated immune response to substances encountered in the workplace. Symptoms include reversible airway obstruction, airway hyperresponsiveness, airway remodeling, mucus production and cellular infiltration into the lung, particularly eosinophilia. The asthmatic response is divided into the induction phase, occurring after initial exposure to allergen, followed by the effector phase where a subsequent exposure to the allergen results in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Additionally, the total cell number in BALF of asthmatic rats was significantly higher than other groups ( P < 0.01, Figure 1), and rats treated with drugs showed substantial decrease compared with asthmatic rats ( P < 0.01, Figure 1). One of the basic features of allergic asthma has been shown to be the eosinophilic airway inflammation [1, 31]. Therefore, eosinophilic percentage was examined as a major biomarker for allergic asthma; our results indicated that drugs used in this study could effectively reduce the eosinophil numbers in BALF ( P < 0.01, Figure 1).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Additionally, the total cell number in BALF of asthmatic rats was significantly higher than other groups ( P < 0.01, Figure 1), and rats treated with drugs showed substantial decrease compared with asthmatic rats ( P < 0.01, Figure 1). One of the basic features of allergic asthma has been shown to be the eosinophilic airway inflammation [1, 31]. Therefore, eosinophilic percentage was examined as a major biomarker for allergic asthma; our results indicated that drugs used in this study could effectively reduce the eosinophil numbers in BALF ( P < 0.01, Figure 1).…”
Section: Discussionmentioning
confidence: 59%
“…Asthma is a chronic inflammatory disease of the airways characterised by eosinophilic infiltration, airway hyperresponsiveness, and structural remodeling [13], along with hemostatic unbalance [4, 5]. Asthma morbidity and mortality have been increasing in recent decades [68].…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested that sihuangxiechai decoction has an effect on the OVA-induced asthma. In addition, Regal [35] and Holgate et al [36] concluded that Eos airway inflammation has been shown to be one of the basic features of allergic asthma. In our study, the percentage of Eos infiltrating in TCM group was significantly decreased in BALF and blood after OVA challenge (Figure 2) compared with the asthma group.…”
Section: Discussionmentioning
confidence: 99%
“…According to Regal (2004), bronchoconstriction in response to antigen is the result of smooth muscle contraction and airway narrowing, and possible factors of airway narrowing are edema, increased vascular permeability and mucus production. It is still necessary for us to clarify via what mechanism(s) Penh was augmented after TMA inhalation challenge in our model.…”
Section: Discussionmentioning
confidence: 99%